Global Id Generation with Verification Based Medical Record Access - K. G. Arunkumar; Deepika B (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The cloud securely stores patient health records, guaranteeing data availability, redundancy, and scalability. To protect sensitive medical data, cloud infrastructure providers frequently use industry-leading security measures. One of the biggest challenges facing modern healthcare is how to securely and quickly share patient health details in an emergency. In order to overcome this difficulty, a revolutionary method that uses the patient’s biometric data and national identity to identify them has been developed, along with a special QR code. Patients’ medical records, which include their personal data, medical history, and prescription information, are kept in a highly secure database that uses blockchain technology and sophisticated security mechanisms. The solution offers distinct QR codes for each patient record, a safe database to store medical data, and national identity with biometric verification for patient identification. Authorized medical personnel have secure portal access to patients’ vital information in the case of data exchange. This method enables other parties (data users) to access patient data in an emergency, guaranteeing prompt and life-saving treatments. Strong authentication procedures, consent procedures, and verification-based data exchange guarantee confidentiality and adherence to pertinent healthcare laws. The project places a high priority on data security, scalability, and usability. It also includes upgrades and ongoing maintenance to keep up with changing security requirements and healthcare technologies. By enabling quick, safe, and accurate access to critical medical data, this system seeks to transform patient care and eventually enhance healthcare outcomes.